CHANGE AND PROCESS MANAGEMENT - Pyykönen, Lauri-Kustaa (My University, 2005)
Throughout the history of the business successful companies have been flexible to meet the demands of the markets. That hasn’t changed, the need of response has come even greater. There are as numerous reasons to go through the change as there are companies doing that. Still there is one thing in common, the change has to be managed. The goal of this study is to describe the effectiveness of change management in Wärtsilä Corporation during the implementation of WE-project (Wärtsilä Enterprise recourse plan-ning). First subgoal is to determine the level of process management awareness in Wärtsilä Finland and Wärtsilä Switzerland. Second subgoal is to clarify the manager’s role during the change process. Third subgoal is to find out how the idea of process man-agement is seen in selected Wärtsilä locations. Studying these topics provides feedback for the management team responsible of conducting the change process. The theory part comes from the literature which concentrates on learning, the concept of change management, and process management. Theory part contains descriptions of dif-ferent approaches towards process management and main ideas about organizational learning and the role of the leader. First these topics are dealt separately and in general but they are combined together in Wärtsilä WE-project case. The aim of this project is to standardize the data systems and way of working in Wärtsilä so that the information can be distributed seamlessly in the whole company regardless of position. The challenge of WE-project lies in the content of the methods and the lack of participating all the needed personnel in the educational sessions about the upcoming change. What comes to the overall picture and development of implementation, it is dragging behind the schedules. Focus point should be in business units and vertical levels which have been neglecting the WE orientated way of working. The process management oriented thinking is not yet rooted in to the organization. When starting the implementation in new companies, management team should focus more on employee’s motivation and education about the WE. Getting correct people with right abilities in to leading positions plays key role in successful implementation and change process.
Keywords: Process management; change management; learning; WE-project; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|